ANTHROPOLOGICAL PERSPECTIVE: SOCIO-CULTURAL ASPECTS OF MEENA TRIBES IN RAJASTHAN STATE, INDIA - Enayatullah Dadmana; Habibullah Haidari b (CV. Radja Publika, 2024)
The tribes are still shrouded in mystery. Almost half of the world's tribal population lives in India. The highest concentration of tribal population is mainly in areas like Rajasthan state. Nearly 14% of Rajasthan's overall population is made up of tribes. The Bhil and Meena tribes are the two largest tribal groups in Rajasthan. The slopes of the Vindhya and Aravalli mountain ranges are home to the majority of Rajasthan's two tribes. The aim of present research is to describe the Society and Culture in transition with Special reference to the Meena Community of Rajasthan. Meena tribes are the most famous tribes in the state of Rajasthan that have their own social and cultural customs and manners, therefore the purpose of this research is to identify the social and cultural customs of these tribes. In order to collect information, the descriptive method was used, and the social and cultural points of these tribes were placed in the charts. The research results show that sociocultural and dietary practices were suitable for their level of life.